The Effect of Pediatric Pyeloplasty in Poorly Functioning Kidneys with Split Renal Function Between 10% to 20%:A Single Institute Experience - Dr. Yasser Fathi Mahdi; Professor Dr. Yousuf Mohammed Al-Hallaq; Dr. Yahia Muhaisin Ali (Academic Journal of Clinicians, 2024)
Background: Management of poorly functioning kidneys with ureteropelvic junction obstruction (UPJO). is controversial, with some recommending direct nephrectomy and others direct pyeloplasty, and others temporary diversion. Objectives: This study aimed to determine the outcome and whether pyeloplasty allows for functional recovery in poorly functioning kidneys in the pediatric age group. Patient and method: A prospective review of 25 patients with unilateral UPJO who underwent open Anderson-Hynes pyeloplasty (AHP). with a split renal function (SRF). 10-20% at Baghdad medical city during the period between December 2019 to September 2022. The changes in the SRF measured by MAG-3 study after 1-year were compared. Results: Mean preoperative SRF was 15.4±2.8% in all cases, which increased significantly postoperatively in success group from 15.5±2.9% to 23.7±4.7%, (P<0.05). , while in two cases with failure, the SRF changed from 13.5±2.1% to 5.5±2.1%. The success rate was 92%, whereas a secondary nephrectomy was necessary for two cases (8.0%). . Conclusion: Poorly functioning renal units with SRF 10% - 20%, can show functional improvement and recoverability, so in these renal units, we cannot rush to do nephrectomy and instead of that we can proceed to pyeloplasty.